1982
DOI: 10.1063/1.92910
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of electron impact ionization in a superlattice: A new avalanche photodiode with a large ionization rate ratio

Abstract: The first superlattice avalanche photodiode (APD) is reported. The high field region of this p-i-n structure consists of 50 alternating Al0.45Ga0.55As (550 Å) and GaAs (450 Å) layers. A large ionization rate ratio has been measured in the field range (2.1–2.7)×105 V/cm, with α/β≃10 at a gain of 10 giving a McIntyre noise factor Fn = 3. The ionization rate ratio enhancement with respect to bulk GaAs and AlGaAs is attributed to the large difference in the band edge discontinuities for electrons and holes at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
3

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(74 citation statements)
references
References 16 publications
2
67
0
3
Order By: Relevance
“…4-6. The claims by Chin et al [2], and by others [3]- [7] that heterojunctions could be used in avalanche regions to reduce excess noise by tailoring the ratio via the band-edge discontinuity, have not been borne out [8]- [17]. Indeed, increasing the aluminum fraction above and hence band-edge discontinuity actually increases excess noise, as shown in Figs.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…4-6. The claims by Chin et al [2], and by others [3]- [7] that heterojunctions could be used in avalanche regions to reduce excess noise by tailoring the ratio via the band-edge discontinuity, have not been borne out [8]- [17]. Indeed, increasing the aluminum fraction above and hence band-edge discontinuity actually increases excess noise, as shown in Figs.…”
Section: Resultsmentioning
confidence: 68%
“…Choice of the layer heterostructure could therefore influence the value of which controls the degree of noisy feedback processes [1]. Subsequent experiments by numerous authors variously supported [3]- [7] or disagreed [8]- [15] with these predictions. However, the most compelling evidence comes from Chia et al [16], [17], who compared multiplication in both homojunction and single heterojunction Al Ga As-GaAs p -i-n diodes and found that the multiplication in heterojunction diodes, and hence the ionization coefficients, were not enhanced over those of corresponding homojunction diodes.…”
Section: Introductionmentioning
confidence: 93%
“…Until recently the optimum case, where k = 0, remained an unachievable theoretical ideal, with most materials exhibiting 0.1 < k < 1. Indeed, unable to identify sufficiently capable materials, some researchers resorted to trying to engineer superlattice structures in which the ionisation coefficients were more disparate (Capasso et al, 1982;Yuan et al, 2000). Beck et al were the first to report APD characteristics consistent with k = 0 in 2001, when they reported results from Hg 0.7 Cd 0.3 Te APDs (Beck et al, 2001).…”
Section: ()mentioning
confidence: 96%
“…(19), it is assumed that [ABI is a c-number in- (13) dependent of the eigenvalues A' and B'. We define Since (A'IeitA IA") = e i EA'6(A' -A") in theA'-rep-F(A', B'), the generalized Wigner distribution funcresentation, CA (Q) in eq.…”
Section: (18)mentioning
confidence: 99%